2020
DOI: 10.1098/rspb.2020.1036
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of cultural tightness in non-industrial societies

Abstract: Human groups have long faced ecological threats such as resource stress and warfare, and must also overcome strains on coordination and cooperation that are imposed by growing social complexity. Tightness–looseness (TL) theory suggests that societies react to these challenges by becoming culturally tighter, with stronger norms and harsher punishment of deviant behaviour. TL theory further predicts that tightening is associated with downstream effects on social, political and religious institutions. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 27 publications
6
76
0
Order By: Relevance
“…Second, this study focused on cultural values using the ten values model of Schwartz. However, other models exist and are widely used, such as the cultural dimensions model [ 54 ], and other cultural factors as cultural tightness (severity of social norms and tolerance for deviance [ 55 ]) have been found to affect the containment of COVID-19 [ 56 , 57 ]. Furthermore, the small size of the indirect effects observed in our mediation analyses suggests that other mediating variables should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study focused on cultural values using the ten values model of Schwartz. However, other models exist and are widely used, such as the cultural dimensions model [ 54 ], and other cultural factors as cultural tightness (severity of social norms and tolerance for deviance [ 55 ]) have been found to affect the containment of COVID-19 [ 56 , 57 ]. Furthermore, the small size of the indirect effects observed in our mediation analyses suggests that other mediating variables should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Later research demonstrated that variation across the 50 United States followed a similar pattern: compared to looser states, tight states had higher death rates owing to natural disasters, greater food insecurity, and more disease prevalence [ 81 ]. Jackson et al [ 82 ] showed that non-industrial societies can also be differentiated on TL, and that ecological threats predict greater tightness. They also found that tightness is correlated with social complexity across cultures, perhaps because social complexity engenders a heightened need for the large-scale cooperation and coordination tightness can provide.…”
Section: Situating Ritualistic Synchrony Within Broader Cultural Evolmentioning
confidence: 99%
“…Recent research on U.S. states has demonstrated the implications of tightness-looseness for infectious disease. Harrington and Gelfand ( 2014 ) reported that tighter U.S. states exhibited higher rates of influenza, pneumonia, and various sexually transmitted diseases, which the authors interpreted as support for the notion that external threats, including pathogens, foster tighter societal norms [see Jackson et al ( 2020 )]. More recent work by Gelfand et al ( 2021 ), however, has argued that tighter societies are more successful at fighting off pandemics, which are much more punctuated events requiring a societal response.…”
Section: Introductionmentioning
confidence: 99%